The life of Webern - Bailey, Kathryn (Cambridge Cambridge University Press, 1998)
On 15 September, 1945 the composer Anton Webern was shot in confusing circumstances in a small mountain village near Salzburg, and the world lost a composer of extreme originality whose mature music was still almost unknown. When Webern's works did come to light he immediately became one of the most influential figures in music of the second half of this century. But the composer who was hailed as the originator of the hyperintellectualised serialism of the 1950s and 60s was by nature an ardent romantic who held feeling - and comprehensibility - to be important above all else in art. This book focuses on several aspects of Webern's life that have been treated only briefly in earlier accounts: his youthful instability, his often embarrassing dependence on Schoenberg, his naive nationalism and his absolute belief in the value of the brief moments of music he produced.